The Impact of Financial Technology on Employee Well-Being in PDAM Jepara: Mediating Roles of Financial Literacy and Lifestyle - Munna, Navis Nailil; Widiastuti, Anna; Riyoko , Sisno (Golden Ratio of Finance Management, 2025)
This research aims to analyze the influence of Financial Technology (FinTech) on Employee Well-Being, both directly and through the mediation of Financial Literacy and Lifestyle, within the context of PDAM Jepara, Indonesia. Using a purposive selection approach, 120 respondents were selected from the population of PDAM Jepara workers to participate in this research. The data was analyzed using Structural Equation Modeling (SEM) with the Smart-PLS version 4.0 tool through outer model testing, inner model testing, mediation testing, and hypothesis testing. The validity test results indicate that the instrument is valid, as evidenced by the loading factor and average variance extracted (AVE) values exceeding 0.7. Additionally, the reliability test results confirm the instrument's reliability with composite reliability and Cronbach's alpha values above 0.7. The research findings demonstrate that Financial Technology positively and significantly affects Employee Well-Being. At the same time, Financial Literacy does not directly influence Employee Well-Being in a significant manner. Moreover, Lifestyle is a significant mediating variable in the relationship between Financial Technology and Employee Well-Being, with a significant positive effect. The findings provide actionable insights for PDAM Jepara management to prioritize FinTech adoption and lifestyle education over financial literacy programs to enhance team members' well-being.